Visual ethics : a guide for photographers, journalists, and filmmakers - Lester, Paul Martin (Routledge, 2018)
Visual Ethics addresses the need for critical thinking and ethical behavior among professionals responsible for visual messages in photography and photojournalism, film, and digital media. From the author of Photojournalism: An Ethical Approach, published more than 20 years ago, this book goes beyond photojournalism ethics. It discusses crucial contemporary concerns, including persuasion, stereotyping, global perspectives, graphic design decisions, multimedia production, social media, and more. Written for an ever-growing discipline, author Paul Martin Lester gives serious ethical consideration to the complex field of visual communication.